Cynara Cardunculus : Use in Cheesemaking and Pharmaceutical Applications - Conceição, C. (2019)
Cynara cardunculus L. is the most widespread species of Cynara genus (f. Asteraceae). This herbaceous perennial plant is native to the Mediterranean region and invasive in other parts of the world, growing naturally in harsh habitat conditions. There are three subspecies: globe artichoke; cultivated cardoon and the progenitor of the two, the wild cardoon. The culture of Cynara cardunculus L. follows an annual growth cycle, emerging in autumn and harvesting in summer. Cynara cardunculus has been considered as a multi-purpose crop due to its relevant biochemical profiles. Inflorescences have been used as food, whereas leaves are a rich source of bioactive compounds. Consequently, larger plants without spines have been selected for technological purposes. Due to its high cellulose and hemicellulose content, the lignocellulosic fraction has been used as solid biofuel, biogas and bioethanol. Both pulp fibers production and seeds oil are suitable for biodiesel production. Over the centuries, the inflorescence pistils of Cynara cardunculus L. have been widely used for cheesemaking. The present chapter gives an overview of the Cynara cardunculus L. emphasizing recent knowledge regarding the use, conservation, preparation and application of Cynara cardunculus in ovine milk cheesemaking, as well as other biotechnological applications.